Phylogeographic analysis of the 2000-2002 foot-and-mouth disease epidemic in Argentina - Brito Rodriguez, Barbara Patricia (2016)
Foot-and-mouth disease (FMD) is a highly transmissible disease of hooved livestock. Although FMD has been eradicated from many countries, economic and social consequences of FMD reintroductions are devastating. After achieving disease eradication, Argentina was affected by a major epidemic in 2000-2002, and within few months, FMD virus spread throughout most of the country and affected >2500 herds. Available records and viral strains allowed us to assess the origins, spread and progression of this FMD epidemic, which remained uncertain. We used whole genome viral sequences and a continuous phylogeographic diffusion approach, which revealed that the viruses that caused the outbreaks spread fast in different directions from a central area in Argentina. The analysis also suggests that the virus that caused the outbreaks in the year 2000 was different from those found during the 2001 epidemic. To estimate if the approximate overall genetic diversity of the virus was related to disease transmission, we reconstructed the viral demographic variation in time using Bayesian Skygrid approach and compared it with the epidemic curve and the within-herd transmission rate and showed that the genetic temporal diversity of the virus was associated with the increasing number of outbreaks in the exponential phase of the epidemic. Results here provide new evidence of how the disease entered and spread throughout the country. We further demonstrate that genetic data collected during a FMD epidemic can be informative indicators of the progression of an ongoing epidemic.